PENGARUH KOMITMEN ORGANISASIONAL DAN MOTIVASI INTRINSIK TERHADAP KINERJA GURU DENGAN DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH - Eni Setiyani, 1352020043; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of Organizational Commitment and Intrinsic Motivation for moderated teacher performance style transformational leadership principals. To test the hypothesis, this study uses empirical jurisdiction with census population data retrieval kuesioner.Komitmen Organizational, Intrinsic Motivation and Transformational Leadership is an independent variable. Teacher performance is the dependent variable. Whereas Transformational Leadership principal is moderating variable. The results showed no significant effect on the commitment of teachers performance while the Intrinsic Motivation and transformational leadership style of principals significantly influence teacher performance. Transformational Leadership Style not moderate the principal of Organizational Commitment on teacher performance but moderate Intrinsic Motivation to teacher performance.Keywords: Organizational Commitment, Intrinsic Motivation, Transformational Leadership and Teacher Performance